Anatomical Study and Clinical Application of Ulnar Artery Proximal Perforator Flaps - Cherubino, Mario; Bolletta, Alberto; Baroni, Tommaso; Di Taranto, Giuseppe; Losco, Luigi; Rubino, Corrado; Valdatta, Luigi (Journal of Reconstructive Microsurgery, 2020)
Background The purpose of this study is to document the vascular anatomy of the free ulnar artery proximal perforator flap and to highlight the possibility of harvesting it based on the perforators originating from the posterior ulnar recurrent artery (PURA), to spare both the main axis of vascular supply to the hand. In addition, we present a case series of five patients treated for soft tissue defects of the hand with free ulnar artery proximal perforator flaps.Methods Ten specimens of anterior forearm were dissected in this study to register number and characteristics of ulnar perforators. The dissection was focused on the perforators originating from the larger branch of the ulnar artery, the PURA, at the proximal third of anteromedial forearm. The anatomical dissections were evaluated in relationship with clinical dissections performed during flap harvesting in five patients.Results In three of the specimens dissected, the proximal perforator originated from the PURA, and in the other seven specimens, it originated directly from the ulnar artery. Five cases of reconstruction of the hand were performed with success using the free ulnar artery proximal perforator flap, and in two cases, the perforator from the PURA was found and it was possible to raise the flap based on this branch of the ulnar artery.Conclusion The free ulnar artery proximal perforator flap can be harvested in two different manners for the same skin island of the forearm. When possible, harvesting it form the PURA allows lengthening of the pedicle. In our experience, this flap presents many advantages such as thinness and hairlessness; it allows preservation of the ulnar neurovascular bundle with an acceptable donor site morbidity. Level of evidence: IV.
Keywords: proximal ulnar artery perforator flap; hand reconstruction; posterior ulnar recurrent artery